1998
DOI: 10.1097/00005344-199810000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Impairment in Nitric Oxide Pathway and Clinical Status in Patients with Congestive Heart Failure

Abstract: A dissociation between basal and stimulated release of nitric oxide (NO) has been found in the peripheral vasculature of patients with congestive heart failure. To explore basal and stimulated NO-mediated vasodilation in patients with heart failure of varying severity, three groups of subjects were studied: group 1, eight normal subjects; group 2, six patients with moderate heart failure; and group 3, eight patients with severe heart failure. Forearm blood flow (FBF) was measured by plethysmography in response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Between each series of drug injections, FBF was allowed to return to its basal value (this required approximately 20 minutes); during these intervals, 0.9% saline was infused. Three drugs were used to explore endothelial function, as previously described 22 : (1) AA indicates controls; SS, patients; NS, not significant; SAP, systolic arterial blood pressure; MAP, mean arterial blood pressure; HR, heart rate; Hb, hemoglobin; Ht, hematocrit; , viscosity. study endothelium-independent vasodilation, at rates of 0.5, 0.8, and 1 g/min; and (3) L-NMMA (Clinalpha, Laufelfingen, Switzerland) at rates of 4, 8, and 16 M/min.…”
Section: Fbf Measurement By Vopmentioning
confidence: 99%
“…Between each series of drug injections, FBF was allowed to return to its basal value (this required approximately 20 minutes); during these intervals, 0.9% saline was infused. Three drugs were used to explore endothelial function, as previously described 22 : (1) AA indicates controls; SS, patients; NS, not significant; SAP, systolic arterial blood pressure; MAP, mean arterial blood pressure; HR, heart rate; Hb, hemoglobin; Ht, hematocrit; , viscosity. study endothelium-independent vasodilation, at rates of 0.5, 0.8, and 1 g/min; and (3) L-NMMA (Clinalpha, Laufelfingen, Switzerland) at rates of 4, 8, and 16 M/min.…”
Section: Fbf Measurement By Vopmentioning
confidence: 99%
“…Impaired shear stress‐mediated, endothelium‐dependent vasodilation in the skeletal muscle circulation during exercise limits skeletal muscle hyperemia and reduces peripheral oxygen delivery and is thereby an important determinant of reduced aerobic capacity in patients with heart failure 8 . Aerobic capacity and functional class correlate with the severity of impairment of endothelium‐dependent, NO‐mediated vasodilation 6,9–12 …”
Section: Role Of Endothelial Dysfunction In Chfmentioning
confidence: 99%
“…In addition, impaired vasodilation in response to endothelium‐derived NO in patients with CHF is partly attributable to hyporesponsiveness of cGMP‐dependent vasorelaxation effector mechanisms in vascular smooth muscle. While some investigators have reported normal vasodilatory responses, 4,15 the majority have found that regional vasodilatory responses to intra‐arterial administration of nitrosovasodilators are significantly decreased in patients with heart failure when compared with normal subjects 5,12,16–20 . Vasodilatory responses to intra‐arterial administration of natriuretic peptides, which mediate vasodilation through activation of particulate guanylate cyclase in vascular smooth muscle, are also attenuated in patients with CHF when compared with normal subjects 21 .…”
Section: Role Of Endothelial Dysfunction In Chfmentioning
confidence: 99%
“…Endothelium-dependent dilation of resistance vessels in response to acetylcholine is impaired in heart failure and related to the clinical severity of the disease [3, 4]. Endothelial dysfunction seems to contribute to the high vascular resistance in the systemic and pulmonary vascular beds of patients with chronic heart failure [3-5].…”
Section: Introductionmentioning
confidence: 99%